Is radiological rotation measurement affected by the fracture pattern in pediatric supracondylar humeral fractures - ŞAHBAT, YAVUZ; BAYSAL, ÖZGÜR; POLAT, MUHAMMED SAİD; BÜYÜKTOPÇU, ÖMER; EROL, BÜLENT; AKGÜLLE, AHMET HAMDİ (My University, 2023)
Background: In supracondylar humerus fractures (SCHF), the most frequently used method to calculate rotation is the Gordon lateral rotation percentage (GLRP) defined by Gordon et al. However, this technique includes only typical fractures (49%–80% of all fractures) from the Johns Hopkins (J-H) fracture classification system. Purpose: The aim of the study was to investigate (1) is Gordon criteria useful for John Hopkins subgroups of supracondylar fractures and (2) is Gordon criteria affected by internal and external rotation. Material and Methods: This study was designed using four pediatric left humerus bones obtained from the Sawbone© company. For each bone, an osteotomy was made to mimic each of the J-H coronal fracture patterns. The cut bones were placed in a wooden rotation apparatus. The GLRP measurements were taken by five blinded observers. Results: In the repeated measurements of the observers, <20° rotation typical and <30° medial oblique and lateral oblique fracture pattern were measured as within the limits of an acceptable amount of rotation according to the Gordon criteria. However, for high fracture pattern (HFP), ≤30° internal rotation and <60° external rotation were determined to be within the acceptable rotation criteria according to the Gordon criteria. Conclusions: All fracture patterns have different characteristics; however, based on the data of this study, the Gordon criteria can be used safely for typical, medial oblique, and lateral oblique fracture patterns but it is necessary to lower the acceptable rate of 50% for HFP.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; fracture pattern; pediatric fracture; Rotation measurement; supracondylar humeral fractures